Self-care practice and associated factors among hypertensive patients who have follow-ups in public hospitals of Bahir-Dar City, Northwest Ethiopia, a mixed study - Gebremedhin Hailu; Muluken Yigezu; Hordofa Gutema; Lydia Melkamu; Natnael Kebede; Elias Assefa; Addis Hordofa (PLoS ONE, 2025)
Background Hypertension is defined as the sustained elevation of blood pressure to levels greater than 140/90 mmHg. It is a leading cause of cardiovascular morbidity and mortality worldwide, accounting for 13% of total deaths and 7% of the global burden of disease. This condition can be significantly reduced by strictly adhering to various self-care practices for hypertension management, including compliance with prescribed antihypertensive medications, reducing salt intake, consuming a balanced diet, avoiding harmful alcohol use, engaging in regular physical exercise, and quitting tobacco smoking. Objectives The aim of this study is to determine self-care practices and associated factors, as well as to explore barriers to these practices among hypertensive patients in public hospitals in Bahir Dar city, Northwest Ethiopia. Methods and materials An institution-based descriptive cross-sectional study, triangulated with qualitative research, was conducted from March 12 to April 12, 2021. A total of 415 participants were selected from three study settings. Data collected from a structured questionnaire were entered into EpiData v3.01 and analyzed using SPSS version 21. Both univariable and multivariable binary logistic regression analyses were performed. The statistical significance of associations between variables was determined using odds ratios with 95% confidence intervals (CIs) and p-values below 0.05. Eight purposively selected individuals participated in the qualitative component of the study. Results Good self-care practices for hypertension were observed in 44.8% of participants. Significant predictors of good hypertension self-care practices included age ≥ 60, education level of secondary school or higher, employment in government positions, controlled blood pressure, good knowledge about hypertension, strong social support, and a positive perceived health status, with Adjusted Odds Ratios (AOR) and 95% Confidence Intervals (CI) of 3.04 (1.26, 7.33), 7.82 (2.79, 21.98), 1.53 (1.53, 14.90), 3.14 (1.70, 5.80), 2.27 (1.17, 4.41), 2.71 (1.31, 5.61), and 2.56 (1.35, 4.85), respectively. Major identified barriers included lack of emotional stability and stress, financial problems, lack of commitment, lack of attention, and inadequate counseling from health professionals. Conclusions Less than half of the participants demonstrated good self-care practices for managing hypertension. Strategies, programs, and guidelines should be developed to help clients understand the importance of multi-dimensional well-being in relation to various aspects of hypertension self-care practices. Furthermore, all patients should receive comprehensive and tailored information on recommended self-care practices and be assessed for barriers to adherence to these practices.